EATURES OF CHANGES IN INDIVIDUAL STATES OF THE NERVOUS SYSTEM OF STUDENTS OF SPECIAL MEDICAL GROUPS IN THE PROCESS OF PHYSICAL EDUCATION - Bezgrebelnaya, E.; Koryahin, V.; Blavt, O. (Вісник Кам’янець-Подільського національного університету імені Івана Огієнка. Фізичне виховання, спорт і здоров’я людини, 2019)
The optimal organization of physical education classes to ensure a high level of somatic health of student youth is relevant for solving the problems of their psychophysical readiness to perform their professional duties. The purpose of the study: to identify the impact of physical education classes in accordance with an individually oriented program for students of special medical groups with diseases in the state of the nervous system to the state of this system. Material and methods. The participants of the experiment were 80 students of the Lviv Polytechnic National University during a three-year physical education course. To determine the effectiveness of a proven program of physical education special medical group for students with diseases in the state of the nervous system, cardiovascular tests have been used. Results. In terms of the general objectives of the study, the experiment can be considered quite effective. After the course of studies, we observe stabilization with a tendency to regress vegetative disorders, improvement of peripheral hemodynamics, against the background of reduction of clinical manifestations of diseases of the nervous system. The final statistical analysis of the obtained control results testifies to the positive dynamics of all the experimental parameters of the experimental group students, the dynamics leveling within 21 %. The quality of the studied parameters of the control group students during the physical education course is characterized by a significantly lower positive trend. Conclusions. The results of the three-year implementation of the physical education of special medical groups of the physical education program for students with diseases in the state of the nervous system showed a significantly higher (p<0.05) effectiveness of the content in the influence on the functional state of the nervous system, compared with the current one. This is reflected in the significant improvement of the studied parameters with experimental groups students compared to control groups students.